Gold-nanorods-siRNA nanoplex for improved photothermal therapy by gene silencing. (February 2016) - Wang, Bei-Ke; Yu, Xue-Feng; Wang, Jia-Hong; Li, Zhi-Bin; Li, Peng-Hui; Wang, Huaiyu; Song, Li; Chu, Paul K.; Li, Chengzhang
Abstract: Nanomaterials-mediated photothermal therapy (PTT) often suffers from the fundamental cellular defense mechanism of heat shock response which leads to therapeutic resistance of cancer cells and reduces the therapeutic efficacy. Herein, a gold nanorods (GNRs)-siRNA platform with gene silencing capability is produced to improve the PTT efficiency. After surface modification, the GNRs show the ability to deliver siRNA oligos targeting BAG3 which is an efficient gene to block the heat-shock response. The synthesized GNRs-siRNA nanoplex exhibits excellent ability in the delivery of siRNA into cancer cells with high silencing efficiency which is even better than that of commercial Lipofectamine 2000. The in vitro and in vivo studies demonstrate the ability of the GNRs-siRNA nanoplex to sensitize the cancer cells to PTT under moderate laser irradiation by down-regulating the increased BAG3 expression and enhancing apoptosis. The GNRs-siRNA mediated PTT has large potential in clinical cancer therapy due to the elimination of therapeutic resistance and enhanced photothermal therapeutic efficacy by means of gene silencing. It also suggests an efficient platform for gene delivery and controllable gene therapy. Graphical abstract: